Comparative study of Janus B2XY (X, Y = S, Se, Te) and F-BNBN-H monolayers for water splitting: revealing the positive and negative roles of the intrinsic dipole. Issue 35 (24th August 2022) - Yan, Xiao-Jun; Li, Wen-Yuan; Nan, Guo-Ting; Zou, Xing; Liu, Li-Li; Wang, Anrong; Wang, Shi-Fa; Wei, Yong; Yang, Chun-Ming; Hu, Lei
Abstract : Water splitting is negatively influenced by intrinsic dipole when VBM is located at the surface possesing a lower vacuum level. Abstract : It is widely recognized that the intrinsic dipole in two-dimensional (2D) photocatalysts promotes hydrogen production during water splitting. Herein, we wonder whether the intrinsic dipole plays a negative role in water splitting. In this work, we make a comparative study of the structural, electronic, and photocatalytic properties of Janus B2 XY (X, Y = S, Se, Te) and F-BNBN-H monolayers using first principles. Our theoretical results reveal that both B2 XY and F-BNBN-H monolayers exhibit spatially separated conduction band minimum (CBM) and valence band maximum (VBM), as well as vacuum level differences at the opposite surfaces due to the intrinsic dipole. The F-BNBN-H monolayer has excellent redox ability for water splitting, because its CBM is located at the surface with a lower vacuum level and its VBM is distributed on the opposite surface possessing a higher vacuum level. By sharp contrast, B2 XY monolayers have limited or vanishing redox ability, because their CBM is located at the surface with a higher vacuum level and their VBM is distributed on the opposite surface with a lower vacuum level. This work emphasizes the negative role of vacuum level differences of photocatalysts caused by the intrinsic dipole in water splitting.